Impact of natural environments on the emotional education of children after the COVID-19 pandemic - Morales Roncal, Angélica Esther (2022)
The covid-19 health crisis left a great challenge in relation to the emotional well-being of children, both for parents and for schools. In this sense, it seeks to integrate them back into a real context, recovering what had been suspended: the right to health, education, contact with nature, spontaneous play, free from fear of contagion and the experimentation of positive emotions; characteristic of affection and socialization. Emotional intelligence is fundamental in human beings because it guarantees a full and healthy lifestyle, which is why the objective of this research is to analyze the impact of natural environments on the emotional education of children, especially after a pandemic context. The result obtained proves that, throughout history, the natural environment contributes to cognitive and emotional development; For this reason, the psycho-pedagogical model of the five socio-emotional competencies that promotes emotional education from schools through playful activities in natural environments has been developed, which favors the development of these competencies and favorable interpersonal ties in children.